Valorization of jackfruit waste into value added products and their potential applications - Pathak, Neelam; Singh, Sangram; Singh, Pankaj; Singh, Pradeep Kumar; Singh, Ranjan; Bala, Saroj; Thirumalesh, Banjagere Veerabhadrappa; Gaur, Rajeeva; Tripathi, Manikant (Frontiers in Nutrition, 2022)
Jackfruit is a potential natural resource for many valuable biomaterials. The wastes from jackfruit are rich in carbohydrate, proteins, fats and phytochemicals. These wastes can be used as feedstock for the development of various bioproducts. The pretreatment strategies involve biological, physical and chemical methods are being used for effective valorization of fruit waste to develop many value added products, like bioethanol, biogas, bioplastics, feeds, functional food additives, and other useful bioactive compounds. Jackfruit peel is also applied in pollution abatement by remediation of dyes color from contaminated environment. Bioenergy production from such renewable resources is an eco-friendly and cost-effective alternative option of fuels, unlike fossil fuels, in future. The efficient bioconversion of waste biomass into useful biomaterials is facilitated by microbial fermentation, and valorization techniques. Therefore, a sustainable technology can be used to develop green economic models for waste utilization. This review addressed the utilization feasibility of jackfruit waste to produce value added products in order to reduce waste and protect environment in a sustainable way.